COVID-19-induced layoff, survivors' COVID-19-related stress and performance in hospitality industry: The moderating role of social support. (May 2021) - Tu, Yidong; Li, Diwan; Wang, Hai-Jiang
Highlights: COVID-19-induced layoff increases survivors' COVID-19-related stress. COVID-19-induced layoff impact survivors' job performance via COVID-19-related stress. Social support moderates the impact COVID-19-induced layoff on COVID-19-related stress. Abstract: The COVID-19 pandemic has hit the hospitality industry hard globally, resulting in millions of employees being laid off. Drawing upon the conservation of resources theory, this study aims to empirically examine how and when COVID-19-induced layoff influences employees' in-role and extra-role performance in the hospitality industry. We tested this model by using field data collected from 302 employees and their supervisors in China across two waves. Results revealed that COVID-19-induced layoff increases survivors' COVID-19-related stress, which in turn leads to decreased in-role and extra-role performance. The strength of these indirect effects is mitigated by perceived family support against COVID-19. Unexpectedly, perceived organizational support against COVID-19 intensifies these indirect effects. The theoretical and practical implications of this study are further discussed.